'history is Like a Coral Reef': a Personal Reflection (Marshall 1963). Issue 1 (1st July 2010) - Cooper, Hilary
Abstract : The idea that Coltham's and Fines' and Rogers' pamphlets appeared out of a vacuum is challenged in the context of primary education. Sybil Marshall's description of teaching history in a village primary school in the 1950s is analysed and many links with these pamphlets are identified: defining the objectives of history education and the processes of historical enquiry based on pupils' questioning of a variety of sources. Coltham's and Fines' and Rogers' work is seen as part of a continuum in which their hypotheses had roots in practice and were followed by empirical studies which explore their hypotheses.